HASIL AUDIT ENERGI DI INDUSTRI TEKSTIL - Achmad Hasan (Badan Pengkajian dan Penerapan Teknologi, 2010)
Energy audit is one way to plan for optimizing the supply and use of energyneeded by the industry. Portrait of the use of electrical energy used in textileindustry supplied from PT.PLN (Persero) with the power contract for 23000 kVAand POJ Power (Mini Hydro Power Plant, Jatiluhur) with installed capacity of5800 kVA. Especially for electric energy supplied from POJ Power, status ofelectricity continues to be a contract with the manager of POJ Power Jatiluhur.Based on the results of measurement of power quality with PQA Hioki 3197 is asdescribed in the previous section, it can be seen that: (a) Voltage magnitude atsome of the panel is high (about 250 V), (b) The power factor is very low, (c)Generally, voltage and current THD (Total Harmonic Distortion) is very high.Kata kunci: energi, listrik, penghematan, filter harmonik, faktor daya